A Standard Approach to Project-Based Learning in a Clinical Informatics Fellowship - Leu, Michael G.; Singh, Angad P.; Lewis, Christopher W.; Jane Fellner, B.; Kim, Theresa B.; Lin, Yu-Hsiang; Sutton, Paul R.; White, Andrew A.; Tarczy-Hornoch, Peter (Applied Clinical Informatics, 2024)
Background The Accreditation Council for Graduate Medical Education suggests that Clinical Informatics (CI) fellowship programs foster broad skills, which include collaboration and project management. However, they do not dictate how to best accomplish these learning objectives.Objectives This study aimed to describe a standard approach to project-based learning for CI, to share its implementation, and to discuss lessons learned.Methods We created a standard approach to project-based learning based on concepts from adult learning theory, the project life cycle framework, the Toyota Production System, and Improvement Science.Results With this standard approach in place, we learned how best to support fellows in its use. In addition to this approach to supporting needs assessment, risk/change management, implementation, and evaluation/improvement skills, we found the need to develop fellow skills in collaboration, leadership, and time management/managing up. Supported by project-based learning using this standard approach, and with targeted project selection to meet topic-based learning objectives, fellows reached the ability to practice independently in 15 to 21 months.Discussion Fellows are uniquely positioned to ensure the success of projects due to their increased availability and protected time compared with attendings. They are readily available for project teams to draw upon their expertise with clinical workflows and understanding of technological solutions. Project-based learning addressing organizational priorities complements fellow project management coursework and improves fellows' ability to function successfully in large, complex, and dynamic organizations. Exposing fellows to contemporary problems, then addressing them through projects, provides fellows with up-to-date applied informatics knowledge.Conclusion Project-based learning can ensure that many general CI learning objectives are supported inherently. It reinforces project management teachings, while providing fellows with a marketable project portfolio to aid with future job applications. Having projects tightly aligned with organizational priorities supports ongoing investment in fellowship programs.
Keywords: medical informatics; medical education; clinical informatics